THE OPTIMAL ANTISEPTIC'S SELECTION FOR PROCESSING BONE CAVITY DURING A SURGICAL TREATMENT OF RADICULAR CYSTS FESTER - V.Y. Potapov; E.N. Vakulenko; Y.D. Protasenko (Ukrainian Medical Stomatological Academy, 2016)
Radicular cysts of the jaws and occur arise in the development of chronic inflammation around the tooth root often. Education radicular cyst is often accompanied by the inflammatory processes. One of the important phases of the treatment of festering radicular cyst is the antiseptic bone cavity after removal of cysts, to prevent the recurrence of inflammatory processes. The object of the article is to study the optimal choice of the antiseptic agents for the bone's defect treatment at the stages of surgical treatment of suppurated radicular cyst. They examined the 46 patients with radicular cysts fester, aged from 24 to 56 years. Of these cysts in the lower jaw were found in 27 patients, the upper jaw had 19 patients. All of the subjects had no comorbidities. We used the data of bacteriological research pus radicular cysts in the examined patients. The puncture of radicular cysts were performed in aseptic. The material was placed in the sterile tube and it was delivered in the bacteriological laboratory for one hour, where planting was carried out and identification of microorganisms isolated from the prevailing colonies in accordance with the methodological guidelines. We used the standard concentration of antiseptic solutions, which are widely used in dental practice in our study: 1% solution dioksidina, 0.2% solution of chlorhexidine 0.02% solution dekasana, 1% solution of betadine, 0 5% solution furatsilini Each of the microorganisms with minimum concentration has an overwhelming impact and was determined. The comparative analysis of the effectiveness determined the individual value of the minimum inhibitory concentration (MIC) and antiseptic activity index (IAA). The composition of the microflora found out the microbial association in all patients during the analysis, which included various ratios of the Staphylococcus epidermidis for 28 patients, the Streptococcus pyogenes for 25 patients, the Klebsiella for 19 patients, the Staphylococcus aureus for 15 patients and the Gramm for 10 patients. Sensitivity was studied with respect to antiseptics 8 strains of Staphylococcus aureus, 47 strains of Staphylococcus epidermidis, 13 strains of Streptococcus pyogenes, 12 strains of Klebsiella, Gramm strains of 15 rods, as well as the family of Candida yeasts. Statistical calculations of data were held by the Student's Exel program. The table shows the index of antiseptik statistics activity for the five test microorganisms. Calculation of (IAA) has allowed us to identify differences in the activity of the individual actions of antiseptic against bacteria in the study. So, we have high levels of (IAA) of 0.02% Dekasana's solution, Betadine - 1%, Chlorhexidine - 0.2%, that point to us the most highest antibacterial effect of these drugs to the microflora of pus radicular cysts according to our study. Thus, these drugs are the most effective antiseptic preparations, when we select antibacterial agents for the treatment of bone cavity at the stages of surgical treatment for supparated radicular cyst.